2018
DOI: 10.1007/s00432-018-2662-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carfilzomib-resistant non-small cell lung cancer cell lines

Abstract: Upregulation of Pgp appears to be an important, but not the only, mechanism of CFZ resistance in NSCLC cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In the case of newer platforms such as TempO-Seq targeted RNA sequencing, there has not been an evaluation of the performance of several normalization methods. Recent publications using the TempO-Seq platform used DESeq2 or CPM for normalization (Grimm et al, 2016;House et al, 2017;Yeakley et al, 2017;Batai et al, 2018;Bushel et al, 2018;Hanke et al, 2018;Limonciel et al, 2018;Chappell et al, 2019;Ramaiahgari et al, 2019;Simon et al, 2019). In this study, we compared seven normalization methods using simulated data from human HepaRG control cells to determine which methods maintained genes at seven assigned FC levels ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of newer platforms such as TempO-Seq targeted RNA sequencing, there has not been an evaluation of the performance of several normalization methods. Recent publications using the TempO-Seq platform used DESeq2 or CPM for normalization (Grimm et al, 2016;House et al, 2017;Yeakley et al, 2017;Batai et al, 2018;Bushel et al, 2018;Hanke et al, 2018;Limonciel et al, 2018;Chappell et al, 2019;Ramaiahgari et al, 2019;Simon et al, 2019). In this study, we compared seven normalization methods using simulated data from human HepaRG control cells to determine which methods maintained genes at seven assigned FC levels ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, by nature of the technology, it lacks 3 end bias. Recently, several studies utilized the TempO-Seq platform for whole transcriptome profiling, primarily for toxicogenomics (Grimm et al, 2016;House et al, 2017;Yeakley et al, 2017;Bushel et al, 2018;Limonciel et al, 2018;Chappell et al, 2019;Ramaiahgari et al, 2019;Simon et al, 2019), but also carcinogenomics (Batai et al, 2018;Hanke et al, 2018), and to profile formalin-fixed paraffin-embedded (FFPE) tissue (Trejo et al, 2019). However, there has not been a comprehensive comparison of normalization methods applied to TempO-Seq data.…”
Section: Introductionmentioning
confidence: 99%
“…12a was coupled with right-hand Boc-deprotected epoxyketone intermediate 4c using the general procedure for the amide coupling reaction to prepare 25 as a white solid (31%). 1 [4,7,10]triazacyclohexadecine-3-carboxamide (26). Macrocyclic carboxylic acid intermediate 15a was prepared from 14a using the general procedure for synthesis of macrocyclic carboxylic acid.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Recently, we reported that iP-targeting linear peptide epoxyketones (e.g., DB-310, Figure b) have a previously unrecognized effect of alleviating cognitive deficits in mouse models of AD in a manner independent of Aβ and tau aggregation. , We also showed that the iP inhibitors lower the levels of serum interleukin-1α (IL-1α) and protect the retinal pigment epithelium (RPE) layer from the structural destruction caused by Aβ-triggered inflammation in Tg2576 mice, potentially representing a new class of AD drugs that aim at a previously untapped pathway in AD drug discovery efforts. Despite promising efficacy, however, these linear peptide epoxyketones’ clinical prospect seems limited at this time due to issues commonly associated with linear peptides, such as poor brain penetration and metabolic instability (mainly attributable to transporter-mediated efflux and enzymatic metabolism). , Yet, the peptide epoxyketone family (“short peptides with C-terminal α′,β′-epoxyketone warhead”) provides an attractive drug development platform for related diseases due to pharmacological advantages conferred by their proven target specificity for the proteasomes and long-term safety in the clinic …”
Section: Introductionmentioning
confidence: 99%
“…Generally, P-gp mediates the resistance of cytotoxic and targeted chemotherapeutics by transporting them out of cancer cells without chemical modification [4]. Previous studies have found that P-gp is overexpressed in resistant breast cancer, lung cancer and colon cancer cells [5,6,7], as well as in patients with neuroblastoma, acute myeloid leukemia, acute lymphoblastic leukemia [8,9,10,11] and many other cancers [12], indicating that it is an important target, the inhibitor of which is emerging as one promising approach to overcome MDR [13,14]. However, the development of such small molecules has been unsuccessful, mainly due to unexpected severe adverse effects and/or low efficacy in improving the therapeutic outcomes as measured in clinical trials [15,16].…”
Section: Introductionmentioning
confidence: 99%